Development of Flipbook Maker-Based E-Module in Economics Subjects to Improve Students’ Interest in Learning - Nur Latifah; Bambang Sunarko; Cut Misni Mulasiwi (Fakultas Ekonomi, Universitas Negeri Semarang, 2022)
The background of this research is the lack of student interest in learning in economics subjects. This study aimed to develop a flipbook maker-based e-module in economics subjects tested from the level of validity, practicality, and effectiveness in improving students’ interest in learning. This research method was research and development (RD). The data used in this study consisted of quantitative data (question scores of material experts, media experts, linguists, educators, and students) and qualitative data (validators’ comments on the product developed). The instruments used in data collection consisted of validation sheets, teacher and student response questionnaires, as well as learning interest questionnaires. The results showed that: the development of a flipbook maker based e-module on economics subject which refers to the Borg and Gall model modified by Sugiyono consisted of ten steps; the validity level of flipbook maker-based e-modules in economics subjects was categorized as valid; the practicality level of flipbook maker-based e-modules in economics subjects was categorized as practical; and the level of effectiveness of flipbook maker based e-modules in economics subjects was categorized as effective in improving student interest in learning.